MODEL-BASED ASSESSMENT AND OPTIMIZATION OF MANAGEMENT STRATEGIES AT A GERMAN CONTAMINATED SITE - Mazo D'Affonseca, Fernando; Finkel, Michael; Maier, Marie-Sophie; Kühne, Manfred (Águas Subterrâneas, 2019)
A site management plan was proposed to control the groundwater contamination at a German metal recovery plant. A model-based assessment and optimization of the proposed strategies was carried out with a numerical groundwater flow model and an innovative model-based optimization technique. The optimization work considerably improved the pumping wells arrangement, allowing a significant reduction of the required number of wells and of their extraction rates, as well as a separated capture of distinct plumes. Transient simulations have also shown that a significant withdrawal reduction may be possible during the German summer months. The optimized contaminated site management strategy can led to expressive cost reductions.